The Poverty Reduction Effect of Social Protection: The Pros and Cons of a Multidisciplinary Approach - Nicky Pouw; Katja Bender (The European Journal of Development Research, 2022)
There is a growing body of knowledge on the complex effects of social protection on poverty in Africa. This article explores the pros and cons of a multidisciplinary approach to studying social protection policies. Our research aimed at studying the interaction between cash transfers and social health protection policies in terms of their impact on inclusive growth in Ghana and Kenya. Also, it explored the policy reform context over time to unravel programme dynamics and outcomes. The analysis combined econometric and qualitative impact assessments with national- and local-level political economic analyses. In particular, dynamic effects and improved understanding of processes are well captured by this approach, thus, pushing the understanding of implementation challenges over and beyond a 'technological fix,' as has been argued before by Ni\~no-Zarazúa et al. (World Dev 40:163–176, 2012), However, multidisciplinary research puts considerable demands on data and data handling. Finally, some poverty reduction effects play out over a longer time, requiring longitudinal consistent data that is still scarce.
Keywords: C18; I13; I31; I32; I38; H53; H55; 330; Social protection; Poverty; Multidisciplinary; Policy instruments; Interaction effects; Spill-over